Binationale Herkunft und Zugehörigkeit Biographische Aushandlungsprozesse junger Erwachsener in Marokko und der Schweiz - Gilliéron, Gwendolyn (Qualitative Fall- und Prozessanalysen. Biographie - Interaktion - soziale Welten, 2022)
The author examines how young adults of binational origin in Morocco and Switzerland repeatedly establish a subjective balance between national discourses of belonging, social processes of inclusion and exclusion, and their own adolescent individuation needs. By means of autobiographical narrative interviews with young adults in both countries and by recourse to Erving Goffman's stigma theory, it is shown that a binational origin is not so much an irritation for the young adults themselves, but rather problematized by society and becomes a challenge.